The globalization project of the Community of Portuguese-Speaking Countries (CPLP) - Herpolsheimer, J.; Seabra, P. (Globalization projects of regional organizations, 2025)
Similar to many other regionalisms that aim to build regions and regional communities, the Community of Portuguese-Speaking Countries (CPLP) emerged as an effort to manage the effects of contemporary globalization processes, trying to gain or regain some control, and to favorably (re)position different state and nonstate actors in reordering processes at different interconnected spatial scales. In that sense, regionalisms and globalization processes have been mutually influencing and, in fact, co-constitutive.